Two Parameter Controller for a Single Machine Infinite Bus System - Ch. Varaha Narasimha Raja (Bulletin of Electrical Engineering and Informatics, 2014)
This paper shows the application of two parameter  controller with internal-Model principle to a single machine- infinite bus system (SMIB), to achieve design specifications and disturbance rejection. In the two parameter model the feedback- compensator is used to achieve required transient response by pole placement and input compensator is used to achieve required steady state response. Finally this method concludes that the method is systematic, general and yields good results.